The tempest :Graphic Novel SHA - McDonald, John.; Shakespeare, William, 1564-1616. (Boston, MA : Heinle, Gengage Learning, 2011)
Presents the play in graphic novel form with a modern English translation, where the wizard Prospero and his daughter Miranda are stranded on an enchanted island and learn about both revenge and forgiveness.
Keywords: Fathers and daughters -- Fiction; Graphic Novel SHA; Shipwrecks -- Fiction; Fathers and daughters -- Fiction; Wizards -- Fiction; Islands -- Fiction; Spirits -- Fiction; Shipwrecks -- Fiction; Graphic novels